THE EFFECT OF MANDELIC ACID ON ACNE-AFFECTED FACIAL SKIN - Čepukova, Enrika; Gierasimovič, Zita (Slauga. Mokslas ir praktika, 2023)
As the technology of cosmetology procedures advances, new substances and hardware appear, the aesthetic meaning of the human body improves. Problematic oily facial skin causes psychological discomfort and affects people's quality of life, worsening their social and emotional wellbeing. Problems with oily facial skin include seborrheic dermatitis, acne.The aim of the study. To evaluate the effect of mandelic acid on facial skin affected by acne.Methods. Mixed method. The study was conducted in February - April 2023. A 23-year-old research participant was selected through targeted selection. The study applied: the method of comparative analysis in assessing facial skin parameters every second procedure. The monitoring method was chosen by evaluating skin changes with the help of the diagnostic device WOOD LAMP. The testing method was chosen by measuring the level of acne prevalence in the epidermis. The client's 4-chapter card was used to collect anamnesis; the use of cosmetic products at home, lifestyle, health and skin condition were examined.Results. After a course of procedures, a lower level of skin inflammation, skin sensitivity, fewer rashes and pigment spots, small capillaries are barely noticeable, only a network of cracked capillaries can be seen in larger areas of the face.Conclusions. Mandelic acids effectively reduce inflammatory processes in facial skin affected by acne, promote faster skin regeneration, and do not cause severe skin necrosis. In the central part of the face, the elements of the rash and the inflammatory area of the skin decreased significantly.
Keywords: acne bacteria; problematic facial skin; mandelic acid